ROLE OF MOTIVATION, WORK DISCIPLINE AND LEADERSHIP ON EMPLOYEE PERFORMANCE - Ingsih, Kusni; Fitri, Yolanda Dwi Ana; Prayitno, Agus (2021)
This study aims to test empirically the effect of motivation, work discipline, and leadership on employee performance. The method used for this study is multiple regression analysis methods. The study population was employees of the Public Works and Spatial Planning Office of Pati Regency. The number of samples determined by the slovin formula was obtained by as many as 80 people. Proportional random sampling as a sampling technique and a questionnaire as a data collection method. The results of the research, either simultaneously or partially showed that motivation, work discipline, and leadership has an positive effect on employee performance. The implication of this research is the importance of motivation, work discipline and leadership to improve the performance of both government employees and private employees.